Relationship Between Process Management Practices And Corporate Sustainable Development In The Malaysian Manufacturing Corporations: The Moderating Effects Of Knowledge Management Capabilities And Environmental Initiatives - Koilpillai, Charis Samuel Solomon (2020)
Over the past two decades, domestic competition and globalization has threatened the growth, profitability and the very survival of many corporations in general. Various studies have shown that corporations need to be concerned with their process management practices to overcome sustainability issues. Thus, process management practices has emerged as an approach for continuous improvement and sustainable development in a systematic manner. Although the significance of process management practices highlights sustainability issues, improves performance and increases corporation market value, little is known about process management and their vast potentials towards corporate sustainable development in the Malaysian context. This study therefore investigates the existence of process management practices and corporate sustainable development in Malaysia, and the moderating effects of knowledge management capabilities and environmental initiatives on the relationship between process management practices and corporate sustainable development. To attain the objectives, this study utilized a survey method to acquire the required information from manufacturing corporations. The survey was carried out among ISO 9001 certified corporations in Malaysia. A total of 213 usable questionnaires were received from the respondents.